2017
DOI: 10.3390/molecules22101729
|View full text |Cite
|
Sign up to set email alerts
|

From 2-Alkylsulfanylimidazoles to 2-Alkylimidazoles: An Approach towards Metabolically More Stable p38α MAP Kinase Inhibitors

Abstract: In vitro and in vivo metabolism studies revealed that 2-alkylsulfanylimidazole ML3403 (4-(5-(4-fluorophenyl)-2-(methylthio)-1H-imidazol-4-yl)-N-(1-phenylethyl)pyridin-2-amine) undergoes rapid oxidation to the sulfoxide. Replacing the sulfur atom present in the two potent p38α mitogen-activated protein (MAP) kinase inhibitors ML3403 and LN950 (2-((5-(4-fluorophenyl)-4-(2-((3-methylbutan-2-yl)amino)pyridin-4-yl)-1H-imidazol-2-yl)thio)ethan-1-ol) by a methylene group resulted in 2-alkylimidazole derivatives 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…One of the most serious limitations of previously reported 2-alkylsulfanylimidazoles is their severe metabolization consisting of oxidation of the thioether function to the corresponding sulfoxide. 48 Nevertheless, in vitro assays performed on compound 44 demonstrated a substantial metabolic stability, as approximately 80% of the unmodified compound was still present after 4 h incubation (Figure S6, Supporting Information ). The major metabolite formed still appears to be represented by the sulfoxide derivative (8.49%), although modifications at the 4-morpholinoaniline substituent might also be present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most serious limitations of previously reported 2-alkylsulfanylimidazoles is their severe metabolization consisting of oxidation of the thioether function to the corresponding sulfoxide. 48 Nevertheless, in vitro assays performed on compound 44 demonstrated a substantial metabolic stability, as approximately 80% of the unmodified compound was still present after 4 h incubation (Figure S6, Supporting Information ). The major metabolite formed still appears to be represented by the sulfoxide derivative (8.49%), although modifications at the 4-morpholinoaniline substituent might also be present.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, additional tests were performed to assess the metabolic stability of methyl-substituted pyridinylimidazole 44 upon incubation with human liver microsomes. One of the most serious limitations of previously reported 2-alkylsulfanylimidazoles is their severe metabolization consisting of oxidation of the thioether function to the corresponding sulfoxide . Nevertheless, in vitro assays performed on compound 44 demonstrated a substantial metabolic stability, as approximately 80% of the unmodified compound was still present after 4 h incubation (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The most prominent example is represented by ML3403, which inhibits the target kinase in the double‐digit nanomolar range and the release of TNF‐α from human whole blood (HWB) in the low‐micromolar range. ML3403 served both as lead compound for further optimization studies and as reference compound in in vitro and in vivo studies . The pharmacokinetic profile of ML3403 was extensively investigated by Kammerer et al .…”
Section: Synthesis Of 245‐tri‐substituted Imidazolesmentioning
confidence: 99%
“…The pharmacokinetic profile of ML3403 was extensively investigated by Kammerer et al . In vitro (animal and human liver microsomes) as well as in vivo (Wistar rats) studies revealed the oxidation of the 2‐methylsulfanyl moiety at the imidazole‐C2 position into a 2‐methylsulfinyl being the predominant biotransformation reaction . Cytochrome P450 (CYP450)‐3A4 was identified to be the key isoform for this sulfoxidation reaction.…”
Section: Synthesis Of 245‐tri‐substituted Imidazolesmentioning
confidence: 99%
“…The metabolic stability of two potent pyridinylimidazole-based p38α mitogen-activated protein (MAP) kinase inhibitors ML3403 and LN950 was improved by Heider et al [ 7 ]. The novel metabolically stable inhibitors were extensively evaluated in various assays and compared to their parent compounds.…”
mentioning
confidence: 99%